Sampan Noodle Restaurant / Fiefi Fariesha Mohamad ... [et al.] - Mohamad, Fiefi Fariesha; Loren, Norhafizah; Kolek, Norshahaziera; Mohd Annuar, Nur Effa Idayu; Julaihie, Nur Fatin Syamimi; Rozui @Rozey, Nurul Qatrunada (University Technology MARA Sarawak, 2018)
SAMPAN NOODLE RESTAURANT is a restaurant which specialized in foods with local taste. Our food and drinks are prepared by our professional chefs and barista who would prepare food and drinks from scratch in the middle of our restaurant. This being said because our restaurant are design and style to “central-kitchen-style”.